Religiosity and Hedonism: A Correlational Study of Santri in the Digital Era - Arnita, Fitri; Fristy, Nada; Mayra, Zara; Syawitri, Melsi; Fadilla, Dina Rizki; Syahputra, Yuda; Brescia, Reggiana (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
In the digital era, the ease of access to information and popular culture through social media has the potential to encourage the emergence of a hedonistic lifestyle, even among santri. This study aims to determine the effect of religiosity on the hedonism lifestyle of Islamic boarding school students. This study uses a quantitative method with a correlational design. The subjects of the study were 150 Islamic boarding school students with a simple random sampling technique. Data collection was carried out through two questionnaires, namely religiosity and hedonism lifestyle and the data were analyzed using simple regression. The results of the analysis showed a significance value of 0.046 (p < 0.05), which indicates a significant influence between religiosity and a hedonistic lifestyle, the hedonistic lifestyle is influenced by religiosity by 2.7%. The higher the religiosity of the students, the lower the tendency towards a hedonism lifestyle.